Argumentos econômicos e sociais no âmbito do direito fundamental à Previdência Social: limites e legitimidade - Pinto, Sabrina Bonfim de Arruda (2018)
The announced financial crisis in social insurance systems around the world has been causing considerable repercussions in the executive, legislative and judicial activities of the Public Power, whose projects, not infrequently, reflect the recurring collision between economic and social arguments in the scope of social security law. In view of such a framework, the present work aims at examining the limits and legitimacies of the state activity to be undertaken in this branch of Social Security, considering, for that, the values inserted in the constitutional text and the factual reality coming from the current economic regime. Following this guideline, the work will be initiated through a brief outline of the evolution of the concept of social protection, from Antiquity to the present, emphasizing the main characteristics of each historical period, as well as the changes that have occurred until the improvement of its meaning in the Social State, and then to present the reasons that justify the fundamentality of Social Security. Then, due to the plurality of disciplines that permeate Social Security and interfere in the stipulation of its legal norms, the relationship between Law and Economics will be evaluated, through an explanation of the discipline called Economic Analysis of Law, with a special focus on the postulates of human rationality and maximum efficiency, so that the applicability of these economic precepts to social security law can be investigated. Continuing in the next chapter, the importance of Social Security for the economic development of a country will be recorded, as will the limitations imposed by the reserve of the financially possible, based on the normative force of the Constitution and on the axiom of proportionality. Already entering the fourth section of the work, a friendly path will be sought that reconciles social protection with the current economic reality, exposing social security projects that fit the present format of the labor market. In the last chapter, we will discuss cases demonstrating the frequent clash between the fundamental right to Social Security and the economic aspects of the respective legal relationship. Regarding the methodology to be used, it will consist of theoretical research of national and foreign doctrine and legislation, as well as the research of the Brazilian jurisprudence and of the statistical data held by the Public Administration. Finally, the work will use the inductive and deductive methods to verify concrete cases and infer rules and solutions to the factual hypotheses investigated